2020
DOI: 10.1002/eap.2131
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the drivers of mortality in African savannah elephants

Abstract: Populations of African savannah elephants (Loxodonta africana) have been declining due to poaching, human–elephant conflict, and habitat loss. Understanding the causes of these declines could aid in stabilizing elephant populations. We used data from the Great Elephant Census, a 19‐country aerial survey of savannah elephants conducted in 2014 and 2015, to examine effects of a suite of variables on elephant mortality. Independent variables included spatially explicit measures of natural processes and human pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In another similar analysis, Schlossberg et al . [36] did not find correlations between elephant mortality and human national human development or governance, although they acknowledge lower statistical power (they focused on savannah elephants in 17 countries while we focus on both savannah and forest elephants across 30 countries). We considered using Schlossberg et al 's [36] measure of poverty (the Night Lights Poverty Index), but most MIKE sites are in rural areas so there is little contrast in light intensity among sites.…”
Section: Discussionmentioning
confidence: 94%
“…In another similar analysis, Schlossberg et al . [36] did not find correlations between elephant mortality and human national human development or governance, although they acknowledge lower statistical power (they focused on savannah elephants in 17 countries while we focus on both savannah and forest elephants across 30 countries). We considered using Schlossberg et al 's [36] measure of poverty (the Night Lights Poverty Index), but most MIKE sites are in rural areas so there is little contrast in light intensity among sites.…”
Section: Discussionmentioning
confidence: 94%
“…Our understanding of natural drivers, such as how rainfall and vegetation variability 13 can drive megafauna population dynamics 13 , seasonal migrations 15,23 , and how megafauna contribute to maintaining savanna heterogeneity 24,27 , is largely based on theoretical works 41 and studies from a few, well studied PAs (e.g., Kruger National Park, South Africa, and the Serengeti National Park, Tanzania 40 ). Likewise, research highlighting the significance of herbivore-livestock interactions 42,43 , fencing proliferation 44 , and land degradation 7 is strongly biased towards the Mara-Serengeti Ecosystem 45 , while cross-continental research has primarily focused on savanna elephants (Loxodonta africana) 46,47 . In addition to local scale studies, some global studies have also indicated improved socio-economic conditions within a country may drive positive megafauna population trends within PAs 48,49 .…”
Section: Natural Vs Human Driversmentioning
confidence: 99%
“…human-wildlife conflict potential) that may influence megafauna biomass across our study area, but are not directly observable at a macroecological scale 46,71,103 (Fig. 1, Table S1).…”
Section: Selecting Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Africa hosted about 1 million elephants in the 1970s but their number had reduced to about 400,000 -630,000 individuals by 2010 (Douglas-Hamilton, 1987;Chase et al, 2016). The dramatic population decline is attributed primarily to poaching, habitat degradation, fragmentation and loss caused by human and livestock population growth and associated land use developments (Ihwagi et al, 2015;Chase et al, 2016;Thouless et al, 2016;Schlossberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%